Hubungan Beban Kerja Perawat dengan Kompetensi Asuhan Keperawatan Spiritual Islami di Unit Hemodialisa - Rika Meliasari; Anggriyana Tri Widianti; Hayinah Rahayu (Universitas Faletehan, 2022)
Nurses as care providers are obliged to meet the needs of patients in a bio psychosocial and spiritual way. The high activity of nurses in serving patients affects their work results, so it is important to pay attention on the workload of nurses in providing nursing services and the competence of Islamic spiritual nursing care. The purpose of this study was to determine the relationship between the workload of nurses and the competence of Islamic spiritual nursing care in hemodialysis unit. This research was a correlational quantitative research by using a cross-sectional research design. The respondents were 24 hemodialysis nurses who were selected by using total sampling technique. The data was collected by online questionnaire. The data analysis used a non-parametric Spearman rank test. This study obtained p-value 0.001 and correlation coefficient 0.628 which indicated a significant relationship between the workload of nurses and the competence of Islamic spiritual nursing care in hemodialysis unit. The researchers recommended that nurses can provide a particular Islamic spiritual nursing care in hemodialysis units since spirituality is highly important for patients with chronic diseases and nurses as care providers are obliged to meet patient needs both psychosocially and spiritually.